Reoccupy Earth : Notes toward an Other Beginning - Wood, David, 1946- (Book collections on Project MUSE., 2019)
Habit rules our lives. And yet climate change and the catastrophic future it portends, makes it clear that we cannot go on like this. Our habits are integral to narratives of the good life, to social norms and expectations, as well as to economic reality. Such shared shapes are vital. Yet while many of our individual habits seem perfectly reasonable, when aggregated together they spell disaster. Beyond consumerism, other forms of life and patterns of dwelling are clearly possible. But how can we get there from here? This text shows how an approach to philosophy attuned to our ecological existence can suspend the taken-for-granted and open up alternative forms of earthly dwelling.